Prepoznavanje neželenih učinkov zdravil na Interni kliniki Univerzitetnega kliničnega centra Ljubljana - Dobravc Verbič, Matej (Farmacevtski vestnik, 2025)
ABSTRACT Pharmacovigilance includes the detection and treat ment of adverse drug reactions and other drug-re lated complications. In the last years, several studies have been conducted at the Centre for clinical toxi cology and pharmacology of the University medical centre Ljubljana, focusing on the recognition and management of adverse drug reactions in internal patients. Particular focus was placed on the assess ment of the causality relationship between suspected adverse drug reactions and the causative drugs. We developed a new causality assessment tool that included the objective Naranjo score and separate expert judgments of the physician and investigators. With the new tool, a larger number of adverse drug reaction cases were assessed as certain. Keywords play an important role in the identification of adverse drug reactions from the patients’ electronic medical records. These include non-specific and specific keywords, drug names and laboratory markers. Un fortunately, most keywords have a low positive pre dictive value. In the future, we would like to imple ment improved software tools that would enable more complex methods of automatized adverse drug reaction search and thus reduce the need for time-consuming manual search methods
Keywords: adverse drug reactions; causality assessment; farmakovigilanca; neželeni učinki zdravi; Neželeni učinki zdravil; ocena vzročne povezanost; pharmacovigilance; Terapevtika; Zdravila